2018
DOI: 10.1103/physrevlett.121.131102
|View full text |Cite
|
Sign up to set email alerts
|

Horizon Hair of Extremal Black Holes and Measurements at Null Infinity

Abstract: It is shown that the conserved charges on the event horizon and the Cauchy horizon associated to scalar perturbations on extremal black holes are externally measurable from null infinity. This suggests that these charges have the potential to serve as an observational signature. The proof of this result is based on obtaining precise late-time asymptotics for the radiation field of outgoing perturbations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 64 publications
0
50
0
Order By: Relevance
“…The physical properties of the thermal bath are modelled by the way we impose boundary conditions, and we shall describe various different well-motivated choices leading to infinite-dimensional near horizon symmetries. We prove that they generically span soft hair excitations in the sense of Hawking, Perry and Strominger [76] (see also [77][78][79][80][81][82][83][84][85]). While our methods are general, we focus on Einstein gravity (possibly with cosmological constant).…”
mentioning
confidence: 75%
“…The physical properties of the thermal bath are modelled by the way we impose boundary conditions, and we shall describe various different well-motivated choices leading to infinite-dimensional near horizon symmetries. We prove that they generically span soft hair excitations in the sense of Hawking, Perry and Strominger [76] (see also [77][78][79][80][81][82][83][84][85]). While our methods are general, we focus on Einstein gravity (possibly with cosmological constant).…”
mentioning
confidence: 75%
“…The proof is a straightforward application of the definitions of H σ,ρ 0 , H σ,ρ 0 , and H σ,1,ρ 0 . We use that the factor (n + 1) 4 appearing in the infinite sums in the definition of || • || H σ,ρ 0 implies control over similar infinite sums with one additional ρ + or ρ c derivative, but no factor (n + 1) 4 . This allows us to conclude that not only m ∈ H σ,ρ 0 , but in fact m ∈ H σ,1,ρ 0 .…”
Section: Gevrey Regularity and Hilbert Spacesmentioning
confidence: 99%
“…In fact, early heuristic and numerical analysis of the linearized problem initiated by Price [44,59,69] suggested that one can do no better than proving inverse polynomial decay estimates, because at sufficiently late times, the leading-order behaviour should be exactly inverse polynomial (this is sometimes referred to as "Price's law"). The presence of so-called polynomial tails in the context of the linear wave equation on asymptotically flat, spherically symmetric black hole backgrounds has recently been proved in a mathematically rigorous setting [4][5][6], where it has moreover been connected to the existence of conservation laws along null hypersurfaces, first discovered by Newman and Penrose at null infinity [65] and discovered in a different guise by Aretakis at the event horizons of extremal black holes 3 [10][11][12][13]. 4 In Fourier space, polynomial tails can alternatively be related to the precise behaviour of resolvent operators corresponding to the wave equation near the zero time frequency, see [48,59,75].…”
Section: Introductionmentioning
confidence: 99%
“…Precise late-time asymptotics were derived in [ 5 ]. These asymptotics led to a novel observational signature of ERN [ 4 ] where it was shown that the horizon instability of ERN is in fact “observable” by observers at null infinity. For a detailed study of this signature we refer to the recent [ 15 ].…”
Section: Introductionmentioning
confidence: 99%